Exploring Direct Written Corrective Feedback on Senior High School Students Compositions - Avendi Perangin Angin; Effendi Limbong; Mardliya Pratiwi Zamruddin (English Teaching Journal : A Journal of English Literature, Language and Education, 2025)
This study investigates the extent to which Direct Written Corrective Feedback (DWCF) enhances the writing accuracy of senior high school students in Indonesia. Drawing from a qualitative case study involving three students of varying proficiency (low, average, and high) at SMK Negeri 1 Muara Wahau, this research examines (1) the types of linguistic errors found in student recount compositions and (2) how DWCF helped students improve across different grammatical features. The findings revealed six error typesrelated to nouns, verbs, tenses, conjunctions, adverbs, and adjectiveswith DWCF proving especially effective in aiding higher-proficiency learners. These results highlight DWCF's pedagogical relevance and suggest differentiated applications based on student needs to improve writing competence in EFL classrooms. DWCF significantly reduced errors among higher?proficiency students, whereas low?proficiency learners showed partial improvement. Pedagogical implications emphasize differentiated feedback strategies and revision cycles.